Hubungan Antara Fungsi Keluarga Dan Kepatuhan Antenatal Care di Wilayah Kerja Puskesmas Juwangi Kabupaten Boyolali Jawa Tengah - Prabaningtyas, Rahayu; , dr. Anika Candrasari, M.Kes; , dr. Mohammad Shoim Dasuki, M. Kes (2015)
Background: Maternal mortality in developing country is still high. Based on UNICEF data at 2012, maternal mortality rate is 228 per 100.000 live births. One of the factors cause high maternal mortality is non-compliance in taking antenatal care during pregnancy. From the preliminary survey in Dinas Kesehatan Boyolali, antenatal visit in district Juwangi still low i.e 60,88%. According to Agustini et al (2013) expectant mothers with a low family support has the possibility of ANC coverage is incomplete 6,363 times. Family has an important role in instilling the motivation for pregnant women because the family is the closest part of them. Aim: To analyze the corelation between family function and complience of antenatal care. Methods: Design of this study using analytic observational with cross-sectional approach. 60 samples taken using purposive sampling method. The samples are post partum mothers on May-August 2014 in Puskesmas Juwangi Boyolali District Central Java. Result: Based on family functions, 34 families (56,7%) were classified as healthy families with 32 pregnant women dutifully carrying out ANC, 22 family (38,3%) were less healthy with 9 pregnant women dutifully, and 4 family (6,7%) were unhealthy with 1 pregnant women dutifully. From statistical tests Spearman obtained r=0,606 p<0,001 (α<0,05). Conclusion: There is significant corelation between family functions and compliance of antenatal care.